2000
DOI: 10.1016/s0029-7844(00)00851-6
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 germline mutations in women with uterine serous papillary carcinoma

Abstract: BRCA1 germline mutations were observed in two of nine of the women in this series. The loss of heterozygosity in the tumor tissue of the carriers, coupled with the high frequency of family and patient histories of breast or ovarian malignancies, suggest that uterine serous papillary carcinoma might be a manifestation of familial breast-ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…However, in this study, 11% of women with UPSC also had a personal history of breast cancer and 29% reported a first-degree relative with breast cancer [34]. Further elucidation into this potential association is of value as it would impact recommendations made regarding risk-reducing surgery, supporting hysterectomy at the time of prophylactic salpingo-oophorectomy [37].…”
Section: Epidemiologymentioning
confidence: 95%
See 2 more Smart Citations
“…However, in this study, 11% of women with UPSC also had a personal history of breast cancer and 29% reported a first-degree relative with breast cancer [34]. Further elucidation into this potential association is of value as it would impact recommendations made regarding risk-reducing surgery, supporting hysterectomy at the time of prophylactic salpingo-oophorectomy [37].…”
Section: Epidemiologymentioning
confidence: 95%
“…In the National Surgical Adjuvant Breast and Bowel Project Breast Cancer Prevention Trial, the largest of these studies, there was no association noted between tamoxifen use and USPC [28,29,[31][32][33]. Several studies have hypothesized a connection between hereditary breastovarian cancer syndrome and UPSC [34][35][36][37]. In a study of 20 Ashkenazi Jewish women with UPSC, 4 were carries of the BRCA genetic mutation, 7 had a personal history of breast cancer and 12 had at least one first-degree relative with either ovarian, breast or colon cancer [36].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Besides finding excessive numbers of male breast cancer (six cases) in six families carrying BRCA2 mutations, Schubert et al also reported two cases of prostate cancer, two cases of bladder cancer, three cases of pancreatic cancer and two cases of fallopian tube carcinoma linked with BRCA1 and BRCA2 mutations [15]. If further investigations confirm the genetic evidence reported by Lavie et al linking uterine papillary serous carcinoma with germline BRCA1 mutations, this disease, too, may prove to be within the spectrum of cancers associated with the HBOC syndrome [121,127] The history of hereditary cancer research has been a history of progressive unveiling of tumor heterogeneity in families that transmit genetic susceptibility.…”
Section: Pathological Considerationsmentioning
confidence: 85%
“…The vast majority of BRCA-associated ovarian cancers are invasive serous lesions. 2,24 Although there are conflicting reports regarding whether BRCA mutations increase the risk of serous cancers of the uterus, 25,26 there is strong evidence to support inclusion of serous fallopian tube cancers in this syndrome. [27][28][29] In the presence of abdominal carcinomatosis, it is often difficult to determine with certainty whether the cancer arose in the fallopian tube or ovary, and some fallopian tube cancers may be misclassified as ovarian, leading to an underestimation of the incidence of fallopian tube cancer.…”
Section: Hereditary Breast and Ovarian Cancer Syndromementioning
confidence: 99%